Lead‐Free Antiferroelectric Silver Niobate Tantalate with High Energy Storage Performance - Zhao, Lei; Liu, Qing; Gao, Jing; Zhang, Shujun; Li, Jing‐Feng (Advanced materials (Weinheim), 2017)
Antiferroelectric materials that display double ferroelectric hysteresis loops are receiving increasing attention for their superior energy storage density compared to their ferroelectric counterparts. Despite the good properties obtained in antiferroelectric La‐doped Pb(Zr,Ti)O3‐based ceramics, lead‐free alternatives are highly desired due to the environmental concerns, and AgNbO3 has been highlighted as a ferrielectric/antiferroelectric perovskite for energy storage applications. Enhanced energy storage performance, with recoverable energy density of 4.2 J cm−3 and high thermal stability of the energy storage density (with minimal variation of ≤±5%) over 20–120 °C, can be achieved in Ta‐modified AgNbO3 ceramics. It is revealed that the incorporation of Ta to the Nb site can enhance the antiferroelectricity because of the reduced polarizability of B‐site cations, which is confirmed by the polarization hysteresis, dielectric tunability, and selected‐area electron diffraction measurements. Additionally, Ta addition in AgNbO3 leads to decreased grain size and increased bulk density, increasing the dielectric breakdown strength, up to 240 kV cm−1 versus 175 kV cm−1 for the pure counterpart, together with the enhanced antiferroelectricity, accounting for the high energy storage density. AgNbO3 lead‐free antiferroelectric ceramic is reported to be a promising candidate for energy storage applications. A great breakthrough with high recoverable energy density up to 4.2 J cm−3 and good thermal stability with minimal variation (±5%) over a temperature range of 20–120 °C is achieved in Ta‐modified AgNbO3 ceramics. This is possible because of the enhanced dielectric breakdown strength and antiferroelectricity.